Developing English Speaking Material for Students in Islamic Junior High School in Kediri - Styawati, Yuslia (JOM, 2023)
This research focuses on addressing the challenges faced by seventh-grade students in Mts Sunan Ampel Ringinrejo, Kediri, related to English language speaking skills. The study involves a comprehensive needs analysis, materials development, and validation processes to create tailored English speaking materials for the specific context of the school. The research method applied in this study follows a Research and Development (R&D) approach that aims to design new products and procedures, which are systematically field-tested, evaluated, and refined until they meet specified criteria of effectiveness, quality, or standards.The needs analysis phase includes interviews with English teachers and questionnaires for students to identify the goals, reasons for choosing English, learning concepts, and existing challenges in the language learning process. The primary issue identified is the lack of relevant and authentic learning materials, hindering students' achievement of language learning objectives. In response to this challenge, the research involves the development of a competence-based syllabus to guide the creation of speaking materials. The final product comprises a syllabus, a teacher's textbook, and a student's textbook for the second semester of seventh grade. In conclusion, the research contributes to the improvement of English language education by providing context-specific speaking materials for seventh-grade students in Mts Sunan Ampel Ringinrejo. The developed materials aim to bridge the gap between theoretical knowledge and practical application, fostering a communicative approach to language learning in the unique setting of the school.